Developing and Validating Tests of Reading and Listening Comprehension for Fifth and Sixth Grade Students in Portugal - Rodrigues, Bruna; Cadime, Irene; Viana, Fernanda Leopoldina; Ribeiro, Iolanda (Frontiers in Psychology, 2020)
An efficient assessment of reading and linguistic abilities in school children requires reliable and valid measures. Moreover, measures which include specific test forms for different academic grade levels, that are vertically equated, allow the direct comparison of results across multiple time points and avoid floor and ceiling effects. Two studies were conducted to achieve these goals. The purpose of the first study was to develop tests of reading and listening comprehension in European Portuguese, with vertically scaled test forms for students in the fifth and sixth grades, using Rasch model analyses. The purpose of the second study was to collect evidence for the validity of these tests based on the relationships of test scores with other variables. The samples included 454 and 179 students for the first and second study, respectively. The data from both studies provided evidence for good psychometric characteristics for the test forms: unidimensionality and local independence, as well as adequate reliability and evidence of validity. The developed test forms are an important contribution in the Portuguese educational context as they allow for the assessment of students’ performance in these skills across multiple time points and can be used both in research and practice.